INTELLIGENCE QUOTIENT MENURUT AL-QUR’AN DAN HADIS - Murjani Murjani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Intelligence Quotient (IQ) has monopolized intelligence theory. A person's intelligence is only measured through the results of intelligence tests, which are logical-mathematical, quantitative and linear. As a result, other aspects of human intelligence are neglected. The hegemony of IQ intelligence theory is inseparable from historical, scientific, and cultural backgrounds. Historically, the IQ theory of intelligence is indeed the first intelligence theory and is more than 200 years old, starting with Gall's Phrenology.